2019
DOI: 10.1007/s00405-019-05355-2
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular density and hypoxia-inducible factor in intraepithelial vocal fold lesions

Abstract: ObjectiveThe promotion of neovascularisation is a crucial aspect of carcinogenesis. The study evaluates the microvascular density (MVD) and expression of hypoxia-induced factor (HIF-1α) in hypertrophic vocal fold (VF) lesions of different histopathological states including non-dysplastic, low-grade, high-grade dysplasia and invasive glottic cancer.Materials and methodsHistological specimens collected from patients diagnosed and treated in a single centre with different histological grades were immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…[ 28 ] Other studies have shown that with the increase of MVD, the rate of tumor formation, invasion and metastasis also increases. [ 29 , 30 ] The results of this study were consistent with the above reports. The expression intensity of AQP1, VEGF and MVD was not related to tumor size, but was closely related to the differentiation, lymph node metastasis, vascular tumor thrombus and clinical stage of gastric cancer.…”
Section: Discussionsupporting
confidence: 92%
“…[ 28 ] Other studies have shown that with the increase of MVD, the rate of tumor formation, invasion and metastasis also increases. [ 29 , 30 ] The results of this study were consistent with the above reports. The expression intensity of AQP1, VEGF and MVD was not related to tumor size, but was closely related to the differentiation, lymph node metastasis, vascular tumor thrombus and clinical stage of gastric cancer.…”
Section: Discussionsupporting
confidence: 92%
“…In our study we assumed the non-dysplastic laryngeal lesions as potential control group for comparison with dysplasia and early invasive cancer. Considering that the hypoxic genetic pathways are commonly activated in hyperproliferative lesions and promote angiogenesis through HIF-1α and that NRP-1 expression is significantly increased in hypoxic tumor microenvironment [ 27 ], together with the results of Rzepakowska et al study presenting immunohistochemical staining of laryngeal specimens for HIF-1α and confirming strong expression of the marker throughout all hypertrophic laryngeal lesions with 60% of stained cells in non-dysplastic lesions, 100% in low-grade dysplasia, 53% in high-grade dysplasia and 50% in invasive cancers [ 12 ], it would be recommended to verify the sNRP-1 and tissue NRP-1 expression in samples from patients without any pathological changes of vocal folds. The sampling of healthy vocal fold mucosa carries however a risk of scarring with permanent voice quality deterioration and is therefore avoided.…”
Section: Discussionmentioning
confidence: 91%
“…Several authors have made the attempt of searching for markers expressed in tissue specimens and/ or in the blood in patients with laryngeal cancer, however no marker has demonstrated a high enough specificity [ 9 11 ]. Angiogenesis seems to be an essential process in the progression of non-dysplastic laryngeal lesions into the dysplasia [ 12 ]. The predictive value of angiogenic factors in laryngeal cancer is the subject of contemporary researches with the majority concentrating on the activity of vascular endothelial growth factor (VEGF) and vascular endothelial growth factor receptor (VEGFR) axis regulated by transcription factors such as hypoxia inducible factor 1α (HIF-1α) and co-receptors such as vascular endothelial growth factor receptor 1 (VEGFR1) and Neuropilins 1 and 2 (NRP 1, 2).…”
Section: Introductionmentioning
confidence: 99%
“…While the fraction of HIF-1α + cells was 18 ± 15% under low-dose conditions, it was 42 ± 11% under high-dose and 31 ± 15% in the control, respectively. According to the categories set up for HIF-1α + cell nuclei reported by Rzepakowska et al [ 48 ], the low-dose PSP-2 results lie in category 1, defined as 1–25%, while the high-dose and control lie in category 2, ranging between 25–50%, respectively.…”
Section: Discussionmentioning
confidence: 99%